National Audubon Society trees of North America : the complete identification reference to trees-- with full-color photographs displaying leaf shape, bark, flowers, and fruit; updated range maps; and conservation status. (Alfred A. Knopf, a division of Penguin Random House LLC, 2021)
"From the creators of the world's most trusted field guides--a go-to source for millions of nature lovers--comes a completely new and unparalleled reference work: the most comprehensive, authoritative, and up-to-date guide to the trees of North America. This master guide is the result of a collaboration between leading scientists, scholars, taxonomic and field experts, photo editors, and designers. An indispensable reference, it covers more than 700 species, with nearly 3,500 full-color photographs--including images of leaf shape, bark, flowers, fruit, and fall leaves. For ease of use, the book includes a glossary and a robust index, and is arranged according to the latest Angiosperm Phylogeny Group classification system--with trees sorted by taxonomic orders and grouped by family, so that related species are presented together. Readers will appreciate the crisp detail of the photographs, range maps (reflecting the impacts of climate change), the physical descriptions, information on fruit, habitat, uses, similar species, and an important new category on conservation status. Essays by leading scholars provide holistic insights into the world of trees. Whether putting a name to the towering conifers spotted along a hike, or trying to determine which pesky tree is encroaching on the patio, readers will come to rely on this work of remarkable breadth, depth, and elegance. It is a must-have reference for the library of any tree-peeper, and is certain to become the number-one guide in the field"--